Design of a seawater-source heat pump for a bridge heating system in winter season - Kutukcu, Gokay; Demir, Hakan (PAMUKKALE UNIV, 2018)
In this paper, a seawater source heat pump system is designed for a bridge heating in winters. It is probable to freeze of the ways and bridges which may cause many accidents in the cold and snowy weathers. Snow melting system is necessary to prevent the possible accidents and privative situations. Design of the optimum pipe length of seawater heat exchanger is a critical issue to transfer the maximum heat from the sea. Effects of the pipe diameter, wall thickness, radius of the coil and coil pitch on the heat transfer were shown in this paper. Moreover, friction factor of the helicoidal pipes and energy consumption of pumps were also calculated.
Keywords: Slinky heat exchanger; Seawater-source heat pump; Optimization; Freezing; EXCHANGER; Engineering